Project Solar House (Oz, 2007)
Project Solar House is Kansas State University’s entry to the 2007 U.S. Solar Decathlon. The Decathlon, coordinated by National Renewable Energy Laboratory (NREL) and the Department of Energy (DOE), is a selective competition that challenges university teams to design and build a small home that is powered solely by the sun.